Comparative Study of Nano‐ZSM‐5 Catalysts Synthesized in OH− and F− Media. (9th August 2013) - Qin, Zhengxing; Lakiss, Louwanda; Tosheva, Lubomira; Gilson, Jean‐Pierre; Vicente, Aurélie; Fernandez, Christian; Valtchev, Valentin
<x xml:space="preserve">Abstract</x> This study reports the seeded synthesis of MFI‐type (ZSM‐5) zeolite in fluoride medium at pH = 8.5. Crystal growth kinetics of the resulting zeolite (ZSM‐5‐F) as a function of seed content and crystallization temperature is studied. The crystallization time is reduced to 1.5 h and crystals with sizes below 200 nm and a Si/Al ratio of 23.6 are obtained. A zeolite with similar characteristics but synthesized in a hydroxyl medium (ZSM‐5‐OH) is used to evaluate ZSM‐5s synthesized in different crystallization media. Their physicochemical properties are compared and particular attention is paid to the nature, number, and distribution of silanol sites. The two zeolites exhibit similar number of Brφnsted acid sites; however the material synthesized in a hydroxyl medium contains a substantially larger number of surface and internal silanols that impact significantly its catalytic performance in methanol to hydrocarbon transformation. While the two materials exhibit similar selectivity in methanol transformations, the catalyst synthesized in fluoride medium shows superior activity and resistance to deactivation. The results suggest that seeded synthesis in a fluoride medium can be used for the preparation of superior zeolite catalysts.